Analisis Implementasi Konektivitas Indihome Untuk Pengguna Smart Meter PLN - Karima, Aisyatul; Enriko, I Ketut Agung (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Smart meters are an integration of ICT in energy meters. The smart meter has a two-way communication feature that allows the operator to read energy data remotely and in real-time. Carrying out remote and real-time monitoring raises several problems including connection costs, coverage area, and the quality of the connection. Based on this background, the formulation of the problem in this study is how to choose effective and efficient smart meter connectivity for customers and how the performance of IndiHome services in the implementation of PLN's smart meters. The purpose of this study is to provide a recommendation system for the selection of an effective connection and propose a new architecture for PLN smart meter customers. This is one of the Internet of things (IoT) implementations to save cost in the use of smart meters. The method used is a literature review, survey, data collection, develop a new architecture, as well as analysis and evaluation of the results. The results of this study indicate that the proposed new IndiHome architecture can send monitoring data from the PLN smart meter device remotely and in real-time and does not incur costs that burden customers.